Development of a Wireless Current Measurement Sensor Node for IoT Applications - Companhoni, Thiago Lehr; Muller, Ivan; Protasio, Cleonilson; Gotz, Marcelo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2018)
This work presents the development of an industrial Internet of Things device for current measurement. It is employed a current transformer that is responsible not only for harvesting energy from an electric load but also as an ordinary sensor for current measurement. After proper energy harvesting, a microcontroller unit reads the current through the circuit using its own analog to digital converter. Then, having the acquired data, it transmits by radio frequency to a receiving device, which in turn sends to the Internet. A supercapacitor is used as a reservoir, so the microcontroller can transmit even in the lack of external energy. Also, the microcontroller unit turn off itself from the harvesting circuit in order to measure the current without any error introduced by its own power consumption. A sub-gigahertz wireless sensor network is implemented using a developed sensor node and a proprietary stack is also developed and presented. The experimental procedure showed the sensor node ability to provide 24 transmissions with no power except from the harvesting circuit.